Practical implications of seat synchronisation - Kleshnev, V. (BioRow, 2024)
Did you know that: Lack of synchronization is counterproductive for the entire crew, as it increases total inertial losses, makes force application less comfortable, and decreases overall efficiency, power production, and rowing speed of the crew.